2022
DOI: 10.1186/s12957-021-02486-x
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the pre-clinical and clinical studies about the use of CAR-T cell therapy of cancer combined with oncolytic viruses

Abstract: Background Cancer is one of the critical issues of the global health system with a high mortality rate even with the available therapies, so using novel therapeutic approaches to reduce the mortality rate and increase the quality of life is sensed more than ever. Main body CAR-T cell therapy and oncolytic viruses are innovative cancer therapeutic approaches with fewer complications than common treatments such as chemotherapy and radiotherapy and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…Carrier cells were targeted at the tumor site and then infected tumor cells by OV replication and lysing, which exerted the maximum effect and effectively avoided anti-viral response. Another study reported that OVs improved the efficacy of CAR-T cell therapy ( Zarezadeh Mehrabadi et al, 2022 ), which suggested a potential method for cancer treatment. Recently, a clinical trial on binary oncolytic adenovirus in combination with HER2-specific autologous CAR VST, advanced HER2 positive solid tumors has been in process (NCT03740256), which might provide more supporting evidence in the OV combination.…”
Section: Discussionmentioning
confidence: 99%
“…Carrier cells were targeted at the tumor site and then infected tumor cells by OV replication and lysing, which exerted the maximum effect and effectively avoided anti-viral response. Another study reported that OVs improved the efficacy of CAR-T cell therapy ( Zarezadeh Mehrabadi et al, 2022 ), which suggested a potential method for cancer treatment. Recently, a clinical trial on binary oncolytic adenovirus in combination with HER2-specific autologous CAR VST, advanced HER2 positive solid tumors has been in process (NCT03740256), which might provide more supporting evidence in the OV combination.…”
Section: Discussionmentioning
confidence: 99%
“…GD2 and B7H3 chimeric antigen receptor (CAR) T cells maintained high metabolic fitness comparable to resting T cells, were highly resistant to exhaustion and have great in vivo efficacy [ 28 ]. Using of the oncolytic viruses along with Ganglioside GD2-specific CAR-T cells to treat the neuroblastoma led to an increase in the attraction and survival of the CAR-T cells [ 29 ]. However, the inconsistency of the results of previous exploratory studies of tumour surface markers highlights the necessity of determining the ideal subgroup of NB patients for immunotherapy, which is still a major challenge in immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The other is through the activation of antitumor immunity. OVs induce immunogenic cell death of tumor cells to release a variety of molecules, including pathogen‐associated molecular pattern molecules (PAMPs), damage‐associated molecular pattern molecules (DAMPs), tumor‐associated antigens (TAAs), and tumor‐associated neoantigens 43 . Tumor cells and immune cells activate the expression of inflammatory factors through PAMPs/DAMPs mode, such as type I IFN, interleukin (IL)−1β, IL‐6, IL‐12, TNF‐α, granulocyte macrophage colony‐stimulating factor (GM‐CSF) 44–46 .…”
Section: Mechanism Of Action Of Ovsmentioning
confidence: 99%